Computed tomography findings in canine cholangiocellular carcinoma. Issue 2 (5th February 2022) - Tanaka, Toshiyuki; Noguchi, Shunsuke; Wada, Yusuke; Nishida, Hidetaka; Akiyoshi, Hideo
Abstract: Although triple‐phase computed tomography is used for differentiating canine liver neoplasms, there is limited information on the computed tomography features of cholangiocellular carcinoma. This retrospective case series assessed the computed tomography features of nine canine cholangiocellular carcinomas. The following computed tomography features were recorded: lesion shape (massive, multiple nodular or diffuse lesions), lesion location, rim enhancement (present or absent), enhancement pattern (stable, progressive or washout), lymphadenopathy (presence or absence) and pulmonary metastasis (presence or absence). Massive lesions, multiple nodular lesions and diffuse lesions were detected in two (22%), five (56%) and two (22%) patients, respectively. Rim enhancement in the arterial phase was observed in eight (89%) patients. Progressive enhancement was detected in six (67%) of the patients. Rim enhancement in the arterial phase and progressive enhancement may be characteristic of cholangiocellular carcinoma in dogs.